Social Media Usage and Development of Psychiatric Disorders in Childhood and Adolescence: A Review - Cataldo, Ilaria; Lepri, Bruno; Neoh, Michelle Jin Yee; Esposito, Gianluca (Frontiers in Psychiatry, 2021)
Social media platforms, such as Facebook, Twitter, and Instagram, are now part of almost everyone’s social life, especially for the newer generations. Children and teenagers grew up together with these Internet-based services, which have become an integral part of their personal and social life. However, as reported in various studies, psychological and psychiatric problems6are sometimes associated with problematic usage of social media. The primary purpose of this review is to provide an overview of the cognitive, psychological, and social outcomes correlated with the problematic use of social media sites during the developmental stages, from 10 to the age of 19. With a specific focus on depression, anxiety, eating, and neurodevelopmental disorders, the review also discusses evidence related to genetic and neurobiological issues, together with the implications in clinical work and future directions under a multidisciplinary perspective. While the scientific community has made significant progress in enhancing our understanding of the impact of social media on teenagers’ lives, more research integrating biological and environmental factors is required to fully elucidate the development of these disorders.